Arabidopsis FHY3/FAR1 Gene Family and Distinct Roles of Its Members in Light Control of Arabidopsis Development - Lin, Rongcheng (American Society of Plant Biologists, 2004)
FHY3 (far-red elongated hypocotyls 3) and FAR1 (far-red-impaired response) are two homologous proteins essential for phytochrome A controlled far-red responses in Arabidopsis (Arabidopsis thaliana). There are 12 additional FHY3/FAR1-related genes in the Arabidopsis genome. The predicted sizes of this family of proteins range from 531 amino acids to 851 amino acids, and they share 12.0% to 82.4% amino acid identities over their entire lengths. In addition, most FRS proteins contain one to three coiled-coil domains and one or two putative nuclear localization signals. Semiquantitative reverse transcription-polymerase chain reaction analyses revealed that all FRS genes except FRS10 are expressed in all tissues examined, including rosette leaves, cauline leaves, inflorescence stems, flowers, and siliques. Analyses of gene specific promoter∷GUS fusion reporter gene expression revealed that all FRS genes except FRS1 are expressed in hypocotyls, and their expression in hypocotyl is induced by far-red light treatment. Transient expression of green fluorescent protein tagged FRS fusion proteins in onion (Allium cepa) epidermal cells revealed that all FRS proteins are targeted into the nucleus. T-DNA knockout frs6 and frs8 mutants flowered early under both long-day and short-day conditions (with much more drastic effects under short-day conditions), suggesting that FRS6 and FRS8 regulate flowering time. In addition, FRS9 RNAi transgenic plants showed a specific hypersensitivity to red light inhibition of hypocotyl elongation and light-regulated gene expression, indicating that FRS9 is a specific negative regulator of phyB signaling mediating seedling deetiolation. In summary, our results support the notion that FRS family members play distinct roles in light control of Arabidopsis development, most likely by regulating nuclear gene expression.